2015
DOI: 10.1614/wt-d-14-00140.1
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian Broomrape (Phelipanche aegyptiaca) Management in Carrot under Field Conditions

Abstract: The chlorophyll-lacking holoparasite Egyptian broomrape is a major threat for many field crops in Israel. In carrot, a high-value crop that is grown year round in Israel, heavy infestation with broomrape can cause severe damage and even total yield loss. The objective of this study was to determine, under field conditions, selective herbicides that would effectively control Egyptian broomrape without damaging the carrots. Ten field experiments were performed between the years 2010 and 2013. The acetolactate sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…A previous study has shown that control of P. aegyptiaca growing on carrots can be achieved by application of low doses of glyphosate to the carrot foliage (Jacobsohn and Kelman, 1980). The findings of that study were confirmed by recent studies in Israel that demonstrated effective glyphosate control of P. aegyptiaca parasitism at different infestation levels under different climate regimes (Cochavi et al, 2015, 2016). …”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…A previous study has shown that control of P. aegyptiaca growing on carrots can be achieved by application of low doses of glyphosate to the carrot foliage (Jacobsohn and Kelman, 1980). The findings of that study were confirmed by recent studies in Israel that demonstrated effective glyphosate control of P. aegyptiaca parasitism at different infestation levels under different climate regimes (Cochavi et al, 2015, 2016). …”
Section: Introductionsupporting
confidence: 79%
“…Therefore, accurate prediction of initiation of P. aegyptiaca attachment is a prerequisite for optimal herbicide application (Cochavi et al, 2016). However, field experiments have shown that the best results are obtained using sequential herbicide application (Cochavi et al, 2015), and it is therefore essential to have in hand a parasitism dynamics model for accurately predicting the timing of herbicide application. Previously developed models are not suitable, as they pertain to short-term crops grown over the summer or greenhouse crops grown mostly under moderately high temperature regimes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was also effective for predicting the entire parasitism dynamics, not only for predicting the first attachment, and could be used for precise temporal chemical management of P. aegyptiaca in carrot (Daucus carota) fields [200]. Three sequential foliar applications of glyphosate at 108 g/ha completely controlled P. aegyptiaca in carrot fields [201,202]. Moreover, applying glyphosate to carrot plants at high temperature injured them and reduced the P. aegyptiaca control efficacy [202].…”
Section: Herbicidesmentioning
confidence: 99%
“…Despite the considerable amount of work that has been devoted to P. aegyptiaca , this parasitic plant still poses a challenge in weed management, particularly because only a few herbicides are available for its control (Eizenberg et al, 2013 ). Among these, the non-selective herbicide glyphosate can efficiently control P. aegyptiaca (Joel et al, 1995 ), even in low doses (Jacobsohn and Kelman, 1980 ; Cochavi et al, 2015 ). Glyphosate inhibits the enzyme 5-enolpyruvyl shikimate-3-phosphate synthase (EPSPS; EC 2.5.1.19) (Steinrücken and Amrhein, 1980 ), a key enzyme in the shikimate pathway and in the aromatic amino acids (AAA) biosynthesis pathway.…”
Section: Introductionmentioning
confidence: 99%